Regional geochemical baselines and controlling factors for trace metals in sediments from the Poxim River, Northeast Brazil - Garcia, Carlos Alexandre Borges (2009)
The Poxim river hydrographic sub-basin comprises four freshwater rivers, Poxim-Açu, Poxim-Mirim, Poxim and Pitanga, and is located in the East of Sergipe State, Northeast of Brazil. The present work investigates the distribution, the factors controlling concentrations, and toxicity risks of the metals Co, Cr, Cu, Li, Mn, Ni, Pb, Zn, Al and Fe, in surface sediments of the four rivers. Toxicity was evaluated using the Consensus-based Sediment Quality Guidelines for freshwater ecosystems. Spearman correlation analysis did not indicate any association of the metals with organic matter, however strong, moderate and weak correlations with aluminium, iron, and manganese, respectively, suggested that clay minerals were the main carrier of metals to sediments. Concentrations of metals in all samples were below the TEC (threshold effect concentration), indicating that for these trace metals adverse effects on aquatic biota should rarely occur. A geochemical baseline for the region was defined using lithium as reference element. Metal enrichments due to anthropogenic influence were only observed at three sites. At other sites, enrichment factors were indicative of a large predominance of naturally occurring metals in the sediments._________________________________________________________________________________________ RESUMO: A sub-bacia hidrográfica do rio Poxim é formada por quatro rios de água doce, Poxim-Açu, Poxim-Mirim, Poxim e Pitanga e está situada na porção leste do Estado de Sergipe, Nordeste do Brasil. Nesse trabalho foi investigada a distribuição, os fatores que controlam as concentrações e o risco de toxicidade para Co, Cr, Cu, Li, Mn, Ni, Pb, Zn, Al e Fe em sedimentos superficiais dos quatro rios. A toxicidade foi avaliada usando o Consensus-based Sediment Quality Guidelines for freshwater ecosystems. A matriz de Spearman não indicou associação dos metais com a matéria orgânica, mas mostrou uma forte correlação com alumínio, moderada com o ferro e fraca com o manganês, sugerindo ser as argilas os principais carreadores dos metais para os sedimentos. Em todas as amostras as concentrações dos metais ficaram abaixo do TEC (threshold effect concentration) indicando que em relação aos metais traço, raramente deve ocorrer efeito adverso para a biota aquática. Foi definida uma base geoquímica para a região usando o lítio como elemento de referência. Somente em três sítios foram observados enriquecimentos dos metais associados a influências antrópicas. Os valores do fator de enriquecimento sugerem uma grande predominância nos sedimentos, de metais de origem natural.